Gender and Capacity Building in Tourism (Case Study in Pentingsari Tourism Village) - Aditya Prayoga, I Ketut; Khairune Nisa, An Nuur; Intan Nurmala Fadin, Delfyan (Jurnal Toursci, 2023)
The role of women in the tourism sector is very important, but in fact in some places still positions women in male dominance, both in quality and quality of work. The development of tourism villages has become a program of the Ministry of Tourism and Creative Economy and one of them is the Pentingsari tourist village. Pentingsari Tourism Village is a community empowerment-based tourism village that has done good women empowerment. This research was conducted to determine gender capacity in tourism development in Pentingsari tourism village seen from psychological, economic, social, and political dimensions. The method used in this study is qualitative method. Data collection in the form of in-depth interviews with managers, field observations and literature reviews from various sources such as books, journals, proceedings, mass media both print and electronic. The results showed that the involvement of women in tourism villages in all lines showed women's response in empowerment ranging from psychological, economic, social, and political dimensions also showed that women had been well empowered. The capacity of women in developing tourism is also high with access to participate in decision making related to tourism in Pentingsari Tourism Village.